Analysis of Students’ Mathematical Critical Thinking Skills – A Case on Two Variables Linear Equation System - Yunita, Nita Sri; Hendriana, Heris; Sugandi, Asep Ikin; Supriatna, Tatang (IKIP Siliwangi, 2026)
Critical thinking is an essential component of mathematics learning, particularly when students are required to solve word problems that demand reasoning, interpretation, and systematic decision-making. However, evidence from previous studies shows that many junior high school students still struggle to apply critical thinking skills effectively, especially in the topic of Systems of Linear Equations in Two Variables (SPLDV). This study aims to analyze the types of errors made by students when solving SPLDV word problems based on indicators of mathematical critical thinking skills. This qualitative descriptive study involved 36 eighth-grade students from SMP Negeri 1 Ciranjang. The data were collected through five open-ended test items developed according to four indicators of mathematical critical thinking: interpretation, analysis, evaluation, and inference. Students’ written responses were scored using an established rubric, and the data were analyzed through the processes of data reduction, data presentation, and conclusion drawing. The findings show that students frequently experienced several types of difficulties, including: (1) failing to identify the known and asked information; (2) using unsystematic problem-solving procedures; (3) constructing incorrect or incomplete mathematical models; (4) applying inappropriate strategies; (5) performing inaccurate or incomplete calculations; and (6) being unable to draw conclusions aligned with the context of the problem. These results indicate that students’ mathematical critical thinking skills related to SPLDV remain weak and require improvement. Therefore, structured guidance, explicit reasoning instruction, and consistent practice are needed to strengthen students’ problem solving abilities.